ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT ISLAM UNIVERSITAS ISLAM MALANG - Diana Hakikah; Nur Hajati; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study was conducted with the aim to determine the effect ofsimultaneous and partial influence of service to the satisfaction of hospitalUniversity in Malang.The population used in this study were all 111 class nurse patients inIslamic University hospital Malang. Sample selection using slovin folmulas.Basedon kereteria, obtained 61 respondents who are samples in this research. Methodused in this research using regression method linear multiple.Based on the results of the analysis can be put forward some conclusionsas follows: 1) Simultaneous direct evidence, reliability, responsiveness,assurance, and attention have an effect on patient satisfaction in hospital ofIslamic University Malang. 2) Partially direct evidence have a positive significanteffect on patient satisfaction in Islamic University hospital Malang. 3) Secarapartial reliability has a significant positive effect on patient satisfaction inhospital Malang University. 4) Secara partial response has a significant positiveeffect on patient satisfaction in Islamic University hospital Malang. 5) Partiallyguarantee has a siginificant in Islamic University hospital Malang. 6) Secarapartial attention has a significant positive effect on patient satisfaction in hospitalIslamic Malang University.Keywords: direct evidence, reliability, response, assurance, attention and patientsatisfaction.